KODE ETIK HAKIM MAHKAMAH AGUNG DAN MAHKAMAH KONSTITUSI - Risky Hidayat Nasution; M. Hasby Al- Fikri; Agripina Nurrahmayani Fradella (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research will describe and summarize the professional code of ethics for supreme court judges and constitutional court judges based on the established code of ethics law. A code of ethics is the moral principles inherent in a profession and is systematically organized. A professional code of ethics is a norm established and agreed upon by a professional group, which directs or instructs its members on how to act, and at the same time ensures that the profession is viewed morally by society. Not all professions will adhere to the same principles. Codes of ethics serve to control society and prevent interference from other parties, prevent misunderstandings and conflicts, and ensure that members of professional groups fulfill their obligations.Its purpose is to maintain the dignity of the profession, safeguard and maintain the welfare of members, enhance the devotion of members, improve the quality of the profession and organization, improve services, strengthen the organization, avoid unfair competition, establish a close relationship with members, and set standards. Important for law enforcers are the principles of humanity, justice, propriety, honesty, and the implementation of the code of ethics.